Assessment of cancers’ diagnostic stage in a Deaf community - survey about 4363 Deaf patients recorded in French units - Vladimir Druel; Hélène Hayet; Laetitia Esman; Marie Clavel; Marie-Eve Rougé Bugat (BMC Cancer, 2018)
Abstract Background Deaf people represent 0.1% of the French population and their access to public health campaigns is limited due to their frequent illiteracy and the infrequent use of sign language in campaigns. There is also a lack of general health knowledge in spite of the existence of French Deaf Care Units (UASS). The aim of this study is to assess the average diagnostic stage of cancer in the Deaf Community and discuss deafness as a contributing factor. Methods Four thousand three hundred sixty-three Deaf patients recorded in five UASS, 80 diagnosed between 2005/01/01 and 2014/12/31 were selected from medical records and/or ICD-10 coding. Data regarding cancers were extracted, grouped by stage and compared to literature. Statistical significance was tested with Fisher’s Exact Test. Results Eighty patients were selected. Most cancers were diagnosed at advanced stages: of 11 prostate cancers, 46% were locally advanced and 18% were metastatic. (In the general population, this was respectively 3% and 10.4% (p < 0.01)). Of six colorectal cancers, 67% were diagnosed at stage III and 33% at stage IV. (Respectively 20.6% and 26.6% (p = 0.03) in the general population). In contrast, of the 15 breast cancers, 93% were diagnosed at stages T1-T3 that was earlier than in the general population (p = 0.43). Conclusion In this study, we observed a delay cancer diagnosis among Deaf people. Complicated and/or non-systematic screening procedures for cancers would be involved. Which is most likely the result of many factors (communication, medical knowledge). Increasing UASS coverage and health information campaigns in sign language could assist in earlier cancer diagnosis.